Tensile deformation behavior of TRIP-aided bainitic ferrite steel in the post-necking strain region. Issue 1 (1st January 2021) - Matsuno, Takashi; Hojo, Tomohiko; Watanabe, Ikumu; Shiro, Ayumi; Shobu, Takahisa; Kajiwara, Kentaro
ABSTRACT: Transformation induced plasticity (TRIP) steels present a remarkable balance of strength and ductility. However, their post-necking hardening behavior, which is required for press-forming and automobile crash simulation, is unreliable because of their stress-triaxiality dependency. Therefore, we analyzed the stress-triaxiality hardening in the post-necking strain regions of tensile loaded TRIP steel to accurately evaluate the stress and strain distribution. Tensile tests were accordingly conducted on small, round-bar specimens to evaluate the true stress vs. cross-sectional reduction ratio curves up to fracture. Additionally, the stress distribution inside each specimen was measured using synchrotron X-ray diffraction. Using these measurements, the hardening law for the TRIP steel was identified through a series of finite element (FE) simulations, in which a simplified phenomenological strain and stress-triaxiality hardening were found to agree well with the measurements in the post-necking strain region. As a result, the hardening rate of the TRIP steel showed a sudden decrease at the uniform elongation limit strain. The FE simulations including stress-triaxiality hardening successfully reproduced this hardening behavior up to the fracture, and the FE simulation including stress-triaxiality hardening and its saturation presented values closest to the XRD measurements. This simulation also agreed well with the measurements obtained in the tensile direction away from the neck center. A microstructural analysis of the retained austenite at the neck supported this result. The FE simulations revealed that a combination of the TRIP effect and its deactivation accelerates the localized deformation at the specimen neck under tensile loading. GRAPHICAL ABSTRACT: Figure 11